PENERAPAN FILSAFAT REALISME DALAM PEMBELAJARAN BERBASIS FAKTA DAN PENGALAMAN NYATA - Kiki Amelia; Ismail (STKIP Subang, 2026)
Realism is one of the most influential schools of philosophy in the field of education. It emphasizes that objective reality exists outside the human mind, and knowledge is obtained through empirical experience and direct observation of the real world. In the context of education, this approach can be implemented through learning activities based on facts and real-life experiences. This article aims to analyze the application of realism philosophy in the learning process and its impact on improving the quality of students’ learning. The writing method used in this study is a literature review of various national and international journals related to realism-based education.